Clinical and Demographic Characteristics of Cutaneous Mastocytosis in Childhood: Single-center Experience. Issue 1 (18th May 2021) - Yazal Erdem, Arzu; Özyörük, Derya; Emir, Suna; Çakmakçi, Selma; Güleç Ceylan, Gülay; Toyran, Müge; Civelek, Ersoy; Dibek Misirlioğlu, Emine
Abstract : Introduction: Mastocytosis is a rare and heterogenous disease, and in children it is generally limited to the skin and tends to regress spontaneously in adolescence. Aim: In this study, demographic, clinical, and laboratory characteristics of pediatric patients with mastocytosis, and also coexisting diseases were investigated. Results: A total of 61 pediatric patients were included in the study. The male-to-female ratio was 2.2, the median age was 2 years (range, 0.25 to 19 y), and the median follow-up period was 2.0 years (range, 0.25 to 19 y). Types of clinical presentation at diagnosis consisted of mainly urticaria pigmentosa (45.9%). Seven patients were further investigated with suspicion of systemic mastocytosis, they were followed up, median of 9 years (range, 2.5 to 16 y), and none of them developed systemic disease. Coexisting allergic diseases were recorded in total 5 patients (8.2%). Three patients had immunoglobulin A deficiency, 1 patient had elevated immunoglobulin E level. A patient developed mature B-cell lymphoma with a heterozygous mutation in c-KIT exon 11. Discussion: Cutaneous mastocytosis in children may present as a complex disease with different clinical signs and symptoms. Standardized clinical criteria and guidelines for the follow-up of children with mastocytosis are required.